1999
DOI: 10.1046/j.1440-1746.1999.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of regenerating liver after partial hepatectomy from carbon tetrachloride hepatotoxicity in rats: Role of hepatic stimulator substance

Abstract: Regenerating rat liver exhibits resistance to CCl4-induced hepatotoxicity, and the protection afforded by the regenerating state can be attributed, at least in part, to HSS-induced increases in mitochondrial respiratory activity and plasma membrane fluidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Indeed, the hepatic stimulator substance can suppress CCl 4 toxicity on mitochondrial membrane fluidity, during rat LR. 41,42 The purified hepatic stimulator substance was renamed ALR, and is considered an important secondary hepatic growth factor inducing mitosis in hepatocytes. 43 This 22-kd protein is the mammalian homolog of the yeast scERV1 gene product, which is essential for biogenesis of mitochondria during the cell cycle and in the maintenance of intact mitochondrial genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the hepatic stimulator substance can suppress CCl 4 toxicity on mitochondrial membrane fluidity, during rat LR. 41,42 The purified hepatic stimulator substance was renamed ALR, and is considered an important secondary hepatic growth factor inducing mitosis in hepatocytes. 43 This 22-kd protein is the mammalian homolog of the yeast scERV1 gene product, which is essential for biogenesis of mitochondria during the cell cycle and in the maintenance of intact mitochondrial genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The 20-dayold male rat pups (NB) known to exhibit extensive liver growth during this early development [14][15][16] were chosen for this study.…”
Section: Models Of Liver Tissue Repair or Liver Regenerationmentioning
confidence: 99%
“…[4][5][6][7][8] Monitoring the markers of liver regeneration in drug overdose victims has been proposed as a prognostic predictor. 5 Under a variety of circumstances in which liver regeneration is stimulated experimentally either by chemical injury (e.g., low dose of thioacetamide, APAP) [6][7][8][9][10] or by surgical resection (two-thirds partial hepatectomy), [11][12][13][14] the liver is known to exhibit resistance toward the higher doses of the hepatotoxicants. Liver cell division during postnatal development in newborns is known to impart resistance against toxicity.…”
mentioning
confidence: 99%
“…Subsequent studies showed that HSS is a heat-stable, ethanol precipitable factor that is able to exert mitogenic effects on primed liver in an organ-specific, but species-non-specific manner [6]. Currently, the participation of HSS in animal models of acute liver injury induced by toxins, such as D-galactosamine [7][8][9], cadmium (Cd) [10][11][12][13], thioacetamide (TAA) [14][15][16][17][18], carbon tetrachloride (CCl 4 ) [19][20][21], and ethanol [22,23], has been investigated. In these studies, variations of HSS activity in the injured liver were noticed [13,15,17,20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, variations of HSS activity in the injured liver were noticed [13,15,17,20,22,23]. Additionally, exogenous HSS administration ameliorated hepatic damage [8, 10-12, 14, 16, 18, 19, 22, 23], enhanced hepatic proliferative capacity post-toxininduced liver injury [7, 8, 11-13, 16, 18, 19, 22, 23], or improved survival of toxin-administered animals [7,9,18,21]. However, HSS activity has not been assessed in animal models of chronic liver injury as in the case of fibrosis and cirrhosis induction.…”
Section: Introductionmentioning
confidence: 99%